Strategi Content Creator sebagai Public Relations guna Membangun Brand Image: Studi Kasus Pada Media Sosial TikTok dan Instagram @asbhoel - Rio Hadi Prawira; Dadi Ahmadi (Bandung Conference Series: Public Relations, 2023)
Abstract. Asbhoel is a company engaged in streetwear fashion. In carrying out its activities, content creators Asbhoel use social media as their media strategy to create a brand image. The aim of this research is to find out how Asbhoel's publication activities are carried out on TikTok and Instagram social media, to find out the steps in the stages of content, to find out how to build an exclusive brand image through TikTok and Instagram social media. The method used in this research is qualitative with a case study approach with a constructivism paradigm. The data collection techniques used were participant observation, in-depth interviews with informants, as well as documentation studies. Supported by triangulation of sources, techniques, time to test the validity of the data obtained by researchers. The results of this study show that the publication activities carried out by Asbhoel were formed from brainstorms obtained from the results of regular meetings with reference to streetwear fashion brands and are supported by the skill and ability of the contest creator team and produce appropriate content messages. Where the content stage includes weekly meeting activities, then supported by team work when cultivating content, and content completion to process the raw results into content ready to be uploaded to Asbhoel's social media. By segmenting content on social media platforms, the exclusive brand image they create is in accordance with the target audience. Abstrak. Asbhoel merupakan salah satu perusahaan yang bergerak dibidang fashion streetwear, dalam melakukan aktivitasnya content creator Asbhoel menggunakan media sosial sebagai media strategi mereka untuk menciptakan brand image. Tujuannya dilakukan penelitian ini yaitu untuk mengetahui bagaimana aktivitas publikasi yang dilakukan Asbhoel pada media sosial TikTok dan Instagram, mengetahui bagaimana langkah dalam tahapan konten, mengetahui bagaimana cara membangun brand image eklusif melalui media sosial TikTok dan Instagram. Metode yang digunakan dalam penelitian ini yaitu kualitatif dengan pendekatan studi kasus dengan paradigma kontruktivisme. Teknik pengumpulan data yang diguakan adalah observasi partisipan, wawancara mendalam dengan narasumber, juga studi dokumentasi. Didukung dengan tringulasi sumber, Teknik, waktu untuk menguji keabsahan data yang didapatkan oleh peneliti. Hasil dari penelitian ini didapatkan bahwa aktivitas publikasi yang dilakukan Asbhoel dibentuk dari brainstorm yang didapatkan dari hasil rapat rutin dengan mengacu pada referensi brand fashion streetwear dan didukung oleh skill and abillity tenaga kerja team contet creator dan menghasilkan content messages yang sesuai. Dimana dalam tahapan konten meliputi kegiatan weekly meeting, lalu didukung dengan team work saat penggarapan konten, dan dilakukannya content completion untuk mengolah hasil mentah tadi menjadi konten yang siap di unggah ke media sosial Asbhoel. Dengan melakukan segmenting konten pada platform media sosial, brand image eksklusif yang mereka ciptakan sesuai dengan target audience.